2012 IFIP Wireless Days 2012
DOI: 10.1109/wd.2012.6402867
|View full text |Cite
|
Sign up to set email alerts
|

A channel-manageable IP multicast support framework for distributed mobility management

Abstract: Abstract-As the rapid increase of Internet traffic is becoming a serious problem, mobile Internet networks are moving towards flat architectures. Distributed mobility management (DMM) is expected to be one of the key technologies tackling the problem by distributing the data traffic concentrated on a centralized anchor to different access routers. For deploying IP multicasting on mobile networks, a Multicast Listener Discovery (MLD) Proxy is generally considered due to its lightweight feature compared to multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Similarly to MLD Proxy usage in PMIPv6, this problem is verified whenever multiple MLD Proxy instances run over a DMM router, since each is associated with a different upstream interface. In order to overcome this issues, in Jeon et al (2012), the coordination between the IGMP/MLD Proxy instances and the serving router was studied, which led to the definition of IP multicast architecture framework applying per-channel management. The simulation results showed that such approach could minimize duplicate traffic by means of a channel control server managing a multicast channel for a given serving router.…”
Section: Related Work On Ip Multicast Support Over Dmmmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly to MLD Proxy usage in PMIPv6, this problem is verified whenever multiple MLD Proxy instances run over a DMM router, since each is associated with a different upstream interface. In order to overcome this issues, in Jeon et al (2012), the coordination between the IGMP/MLD Proxy instances and the serving router was studied, which led to the definition of IP multicast architecture framework applying per-channel management. The simulation results showed that such approach could minimize duplicate traffic by means of a channel control server managing a multicast channel for a given serving router.…”
Section: Related Work On Ip Multicast Support Over Dmmmentioning
confidence: 99%
“…This protocol design may lead to duplicate traffic, where a serving DMM router receives multiple copies of the same multicast stream, one for each IGMP/MLD Proxy instance running on the router. Aiming to solve this issue by tackling the lack of coordination between the IGMP/MLD Proxy instances and the serving router, a channel-manageable IP multicast architecture framework has been presented in Jeon et al (2012). It solves the duplicate traffic issue by introducing a channel control server managing a multicast channel for a given serving router.…”
Section: Introductionmentioning
confidence: 99%
“…In [16], the authors introduce a framework managing all multicast channels and controlling which channel should be local or remote. In other words, the MAR will decide to get a multicast channel from the multicast infrastructure (for local content) or from the previous MAR (for remote content) to minimize the multicast traffic duplication.…”
Section: ) Tunnel Convergence Problem and Sub-optimal Routingmentioning
confidence: 99%
“…A set of proposals has been introduced (mainly for PMIPv6) in which each of them aims at solving a couple of issues, for example: i) the multicast context transfer (CXT) for the service disruption and packet loss issue [11] [12]; ii) the multiple upstream interfaces support for the Internet Group Management Protocol (IGMP) / MLD Proxy for the tunnel convergence problem [13]; iii) the explicit tracking function for leave latency and waste of resources issue [14] [15]; and iv) the channel-manageable solution for both tunnel convergence and sub-optimal routing issue [16]. Yet, they fail to address all these issues at the same time.…”
Section: Introductionmentioning
confidence: 99%